2019
DOI: 10.1016/j.jnn.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Listening to the parent voice to inform person-centred neonatal care

Abstract: Listening to the parent voice to inform person-centred neonatal care. AbstractFamily integrated care (FIC), where parents are an integral part of their baby's care and decision-making can enhance parental involvement and empowerment, contributing to decreased parental separation and stress. It follows that parents can also be a central part of neonatal education for staff in the neonatal speciality. This paper focuses on what students and staff can learn from parents about what they feel is important to make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Acknowledging this balance is important (Petty et al, 2019b). Beating the odds and battling through, for example, were positive threads amongst the turmoil and stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acknowledging this balance is important (Petty et al, 2019b). Beating the odds and battling through, for example, were positive threads amongst the turmoil and stress.…”
Section: Discussionmentioning
confidence: 99%
“…This study in context, as a component of a larger one, is depicted in Figure 1. The other study components are reported separately (Petty et al, 2019a, 2019b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Making meaning of such events and how they integrate into a mother’s life framework can be important for her well-being and adaptive functioning. 18, 19 In addition, mothers’ narratives provide unique insights into nuances of their experiences, which may not be captured on questionnaires, 4, 10, 20-23 and may point to avenues for intervention. Several qualitative studies have examined maternal narrative experiences of having an infant in the NICU and the transition home upon hospital discharge, 24, 25 results from which have informed interventions targeting maternal well-being.9,26 In brief, these studies describe the stress, uncertainty, and challenges mothers of preterm infants may experience while in the NICU, as well as barriers to and facilitators for maternal coping, mental health, and attachment during the NICU experience.…”
Section: Introductionmentioning
confidence: 99%
“…Several qualitative studies have examined maternal narrative experiences of having an infant in the NICU and the transition home upon hospital discharge, 24, 25 results from which have informed interventions targeting maternal well-being.9,26 In brief, these studies describe the stress, uncertainty, and challenges mothers of preterm infants may experience while in the NICU, as well as barriers to and facilitators for maternal coping, mental health, and attachment during the NICU experience. 9, 26 Most, but not all, 19 studies to date have examined maternal narrative experiences of having a preterm infant during the postpartum period, which for some, may be colored by an acute stress response.Narratives from the postpartum period cannot examine mothers’ experiences later families benefit from in the first years of their child’s life, including the impact of the NICU experience on mothers’ later well-being. Mothers of former preterm infants have been found to experience greater feelings of vulnerability, persisting through the preschool years.…”
Section: Introductionmentioning
confidence: 99%